Analiza porównawcza struktury przychodów ze sprzedaży w przedsiębiorstwie wielooddziałowym - Nowak, Edward (Comparative Analysis of Sale Revenue Structure in a Multidivisional Company, 2006)
The article contains an analysis of the revenue structure in a multidivisional company. In the paper the use of taxonomie methods in a comparative analysis of structure of revenue are presented in different divisions of a company. The methodic points are illustrated by an empirical example of a company offering products and services.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 179-186